EVALUATION OF LAPAROTOMY SURGERY WOUND HEALING IN DOGS USING THERMOGRAPHIC ANALYSIS - Wijayanti, Agustina Dwi; Purnomo, Agus; Wijayanto, Hery (Jurnal Kedokteran Hewan, 2023)
This study aimed to develop the use of thermographic analysis to evaluate wound healing for laparotomy surgery in animals. The experiment used nine adult dogs 5 males and 4 females, bodyweight 5-10 kg) that had undergone the same general anesthesia and laparotomy procedures. Evaluation of wound healing was performed at 24, 48, and 72 hours after surgery and 7 days after operations using a digital thermal camera. During each thermographic evaluation period, blood samples were taken for analysis of total leukocytes and leukocyte differential. The results of thermal imaging were compared with the values of inflammatory cells and the clinical condition of wound healing. Comparison of thermographic analysis with inflammatory status was evaluated using the regression equation and showed a strong correlation coefficient (Y= -0.4847 + 40.14, R2= 0.867), that is, the higher the temperature, the lower the inflammation. The conclusion of study is that thermographic analysis can be used to evaluate wound healing of laparotomy surgery in dogs.